The functional parallelism of transformed verbal constructions in Slovak and in French - Chovancova - Simona Krafcikova, Katarina (Romanica Olomucensia, 2020)
The paper deals with selected types of syntactic constructions of verbs in Slovak and in French. The focus is on the impersonal reflexive use of the Slovak third-person singular (A) and its correspondence with first-person generic plural constructions (B) of the same Slovak verbs. The third type of verbal construction under focus is the French "on"-subject construction (C). The corpus-based study is conducted using the Slovak National Corpus and the French corpus Frantext on a narrowed sample of 12 Slovak verbs of sight and their French semantic counterparts. Occurrences of A and B constructions were excerpted from the corpus. Once their frequencies had been assessed, five core Slovak verbs of sight were treated further to verify the hypothesis of the interchangeability of A and B. The verification took the form of a substitutional test in authentic contexts. In the final step, the interchangeability of A/B and C was checked. The interchangeability of A and B was confirmed in two-thirds of the sample. Differences were shown between different hyponymic groups established in the sample set. Functional parallels between A and B proved to be linked to specific pragmatic values of the verbs that were studied. In relation to the functional parallelism between A/B and C, exemplification demonstrated that C remains, together with the passive, one of the two main French functional equivalents of Slovak agentless constructions. The paper is a contribution to a larger contrastive research study on verbal transformations aimed at the conception of a valency transformation grammar of Slovak and French with potential impacts on translation and language teaching.
Keywords: grammar; verb; valency; agent; Slovak; French